Knowledge of the inhabitants of the Mid-Araguaia region, Mato Grosso State, about the usefulness of bee (Hymenoptera, Apidae) products - DOI: 10.4025/actascibiolsci.v31i4.4518 - Souza, Sebastiana de (2009)
The objective of this study was to find out the use indications for bee products. The interviews were carried out with representatives of 14 municipalities of the Mid-Araguaia River region, Mato Grosso State, Brazil, during the months of January and February 2007. In the Mid-Araguaia there were indications of use honey, beeswax, poison and propolis, mainly for medicinal purposes. Honey was the most used product (75.49%). The consumption is mainly by ingestion (79.59%) and in natura (71.43%). The bee products are used, by the majority of the users, for medicinal purposes (77.55%), and they are recommended to heal throat infections (63.27%)